The Practice of Ṣiḥah Marriage among the Rifa'iyah Congregation in Sociological and Islamic Marriage Law Perspectives - Prasetyo, Anggi; Muhsin, Ilyya (Universitas Islam Negeri Raden Intan Lampung, 2023)
This article examines the practice of repeating marriage contracts (ṣiḥah marriage) among the Rifa'iyah Congregation in Wonocoyo Village, Wonoboyo, Temanggung, Central Java. This repetition was carried out by Rifa'iyah Kiyais as representatives of female marriage guardians to perfect the marriage contract which had been carried out previously in the presence of officers from the Office of Religious Affairs (KUA). This research is classified as qualitative field research using a sociological approach. The aim is to examine this social phenomenon from the perspective of Social Construction theory and the perspective of Islamic Law. This research found that the practice of ṣiḥah marriage among the Rifa'iyah congregation of Wonocoyo Village was formed through several stages, namely: the externalization stage, the stage of conveying the practice of ṣiḥah by Rifa'iyah Kiyais, the objectification stage, the stage of forming objective reality, and the internalization stage, the stage of absorption of the objective world into the individual consciousness of the Rifa'iyah Congregation. In the view of Islamic Marriage Law, the practice of ṣiḥah by the Rifa'iyah congregation is similar to tajdīdun nikāḥ (renewal of the marriage contract) which, according to Jumhur ulama', is permissible simply because of ihtiyāth (caution).